Acute hemorrhage within intradural extramedullary schwannoma in cervical spine presenting with quadriparesis - Ranjan Kumar Sahoo (Journal of Craniovertebral Junction and Spine, 2015)
Schwannoma with acute hemorrhage is rarely seen. A 44-years-old male patient presented with complaint of neck pain and acute onset of quadriparesis. Magnetic resonance imaging (MRI) of his cervical spine revealed evidence of an intradural extramedullary tumor with intratumoral acute hemorrhage. He was operated in emergency and the mass was found to be schwannoma with acute hemorrhage. Post operatively the patient improved significantly. Though schwannomas show microscopic intratumoral hemorrhage and necrosis at times, schwannoma with acute hemorrhage resulting acute onset of neurological deficit is very uncommon.